Analysis Of Raw Material Inventory Forecasting Using The Time Series Method At UD. Tunas Baru, Gunungsitoli City - Perubahan Waruwu; Sophia Molinda Kakisina; Jeliswan Berkat Iman Jaya Gea; Robin Markus Putra Waruwu (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the application of the time series method using the Moving Average approach to forecast raw material requirements at UD. Tunas Baru, Gunungsitoli City. The company has traditionally managed its inventory without a systematic calculation basis, resulting in fluctuating purchases and usage that cause overstock and shortages. This research employed a descriptive quantitative method using data on wood board purchases and usage from January to December 2024.The results show that the Moving Average (3-period) method provides a general overview of raw material demand trends, although it remains less accurate in capturing sharp fluctuations. The Mean Squared Error (MSE) value was 27,338 (sheets²), indicating a relatively high deviation between actual and forecasted values.These findings suggest that time series-based forecasting can serve as a preliminary foundation for raw material planning at UD. Tunas Baru. Applying an appropriate forecasting method can help the company minimize inventory imbalance risks and improve production efficiency. It is recommended that the company implement a data-based inventory management system and consider more adaptive forecasting methods such as Weighted Moving Average or Exponential Smoothing.